Information Linkages Among BRICS Countries: Empirical Evidence from Implied Volatility Indices. (December 2019) - Sharma, Gagan; Kayal, Parthajit; Pandey, Piyush
In this article, we examine the information linkages of the forward-looking measure of volatility, the volatility index (VIX), for underlying equity market indices of BRICS countries—Brazil, Russia, India, China and South Africa. A study of the information transmission process confirmed a long-run equilibrium relationship between pairs of BRICS countries. The multivariate generalised autoregressive conditional heteroscedasticity (MGARCH) model revealed strong intertemporal linkages between sample VIX. Return and volatility spill-over matrix show the varying degree of connectedness of BRICS VIX across the study period. This study contributes to the international finance literature and has important implications for investors, portfolio managers, policymakers and academia. JEL Classification: C58, F36, G11, G14, G15